Sustainable transport : planning for walking and cycling in urban environments - Tolley, R. S. 1946- (Woodhead Publishing Limited : CRC Press, 2010)
Cycling and walking are both essential components in sustainable transport strategy and are becoming an ever more important part of urban planning. There is now a wealth of international experience of how well sustainable planning works in practice and how it can be improved. With a wide range of contributions from America, Australia, Europe as well as the UK, Sustainable transport sums up many of the lessons learnt and how they can be applied in improved planning. Non-motorised transport planning depends on combining improvements to infrastructure with education. There are chapters examining both national strategies and local initiatives in cities around the world, including such topics as changes to existing road infrastructure and the integration of cycling and walking with public transport. Since education is a critical element in sustainable transport planning, contributors also consider such topics as developing healthier travel habits and ways of promoting cycling and walking as alternatives to the car. With its blend of practical experience and suggestions for improvement, Sustainable transport is essential reading for urban planners, environmental groups and those researching transport issues. Comprehensive handbook covering sustainable transport initiatives world wideFocuses on walking and cycling as alternatives to motorised transport systemsPresents practical advice on how to encourage sustainable transport schemes.
Keywords: Urban transportation policy.; Bicycle trails.; Sustainable development.; Pedestrians.; Transportation -- Environmental aspects.; Sidewalks.; Bicycle lanes.; elektronické knihy; electronic books